Social Media Intelligence (SOCMINT) within the South African context : a theoretical and strategic framework for the national security environment - Stegen, Johanna Isabella (North-West University (South Africa), 2019)
We are currently living in a complex global environment where change is a given, constantly fuelled by the increasing pace of technological development. These developments affect every aspect of society, including business, education, communication and government. One of the most significant technological developments in recent decades, especially in relation to information communications, is the rise of the internet. This development has brought with it an information revolution that increased the amount of available information, enhanced access to information and reduced the cost of communication. One of the most significant developments associated with the internet is the emergence of social media, which changed traditional communication, augmented social interaction and made state boundaries irrelevant. The phenomenon of social media plays a key role in the production and dissemination of information and people‟s access to it. Characteristics such as interactivity, affordability, availability, facelessness and a lack of censorship have increased the use of social media as a tool of communication. These same characteristics also make it attractive to terrorist and other criminal organisations. The implications for national security make social media important for intelligence organisations. This new development motivated this study. Social media provides the intelligence community with a vast quantity of information (SOCMINT) that could be of importance in safeguarding national security. However, the intelligence community in South Africa is not using this tool to its full potential. The primary aim of this study was to develop a strategic framework for the national security environment in South Africa that includes SOCMINT as a source of information. The secondary aim was to contribute to the theoretical foundation for intelligence studies. This is a young academic field with a limited theoretical foundation and the detailed meta-theoretical discussion in this study adds to the theoretical base of intelligence studies. The proposed framework could enrich the activities of the intelligence community and enhance the intelligence product delivered to the client. This in turn will help ensure the intelligence organisation‟s relevance in this global environment of information overload.
PhD (Development and Management), North-West University, Potchefstroom Campus
Keywords: Apartheid; Communication studies; Cyber space; Digital age; Intelligence; Intelligence studies; International studies; Internet; National security; New media studies; Political science; Political science; Security studies; SOCMINT; Social media; Surveillance; Technology